Роль виявлення мутації BRAF V600E під час проведення ТАПБ вузлів щитоподібної залози - Хоперія, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2011)
TheBRAF mutation is specific for thyroid papillary cancer (PTC) and correlates with PTCs invasiveness. Detection of BRAF mutation on fine needle biopsies (FNAB) can improve accuracy of cytological diagnosis in patients with thyroid nodules. This study investigated whether detection of BRAF mutation can be performed on routinely stained FNABs. One hundred thirty four FNABs samples stained by MayGrunwald/Geimsa technique were classified as suspicious (30 cases) or malignant FNABs (104 cases). Postoperative diagnoses were 10 benign and 124 malignant tumors. In suspicious FNABs, BRAF mutation was found in 2/30 (6%) of cases (2 PTC). In malignant FNABs, BRAF mutation was detected in 47/104 (45.2%) There was a significant association of BRAF mutation in preoperative FNAB specimens with the presence of extrathyroidal extension and lymph node metastases. Stained FNAB specimens can be used for DNA extraction and assessment of BRAF mutation. Detection of BRAF mutation has a limited value in diagnosis of malignancy in cases of suspicious FNABs. In malignant FNABs, detection of BRAF mutation could be a useful adjunct for preoperative identification of tumors with a high risk of extra-thyroidal extension and metastases.